1996
DOI: 10.1002/j.1460-2075.1996.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a PY motif in the epithelial Na channel subunits as a target sequence for mutations causing channel activation found in Liddle syndrome.

Abstract: Liddle syndrome is an autosomal dominant form of hypertension, resulting from mutations in the cytoplasmic C‐terminus of either the beta or gamma subunits of the amiloride‐sensitive epithelial Na channel (ENaC) which lead to constitutively increased channel activity. Most mutations reported to date result in the elimination of 45–75 normal amino acids from these segments, leaving open the question of the identity of the precise amino acids in which mutation can lead to an enhanced channel activity. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
283
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(310 citation statements)
references
References 18 publications
18
283
1
4
Order By: Relevance
“…Results of alanine scanning mutagenesis within this region in the presence of an intact ␤ subunit PY motif suggested that this region did not participate in the control of amiloride-sensitive currents in channels with otherwise intact C termini (35). However, it is possible that this region is involved in channel regulation under specific conditions, such as in the presence of arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Results of alanine scanning mutagenesis within this region in the presence of an intact ␤ subunit PY motif suggested that this region did not participate in the control of amiloride-sensitive currents in channels with otherwise intact C termini (35). However, it is possible that this region is involved in channel regulation under specific conditions, such as in the presence of arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Because the Nedd4-2-mediated inhibition of ENaC requires the presence of PY motifs in the C termini of ENaC, we tested the effect of SGK1 on mutated ENaC channels with C-terminal deletions in all three subunits. The sites of the C-terminal truncations were analogous to the original Liddle's syndrome mutation of the ␤-subunit and resulted in the loss of all PY motifs (36). As shown in Fig.…”
Section: Deletion Of the C Termini Of All Three Enac Subunits Abolishmentioning
confidence: 93%
“…Those encoding the truncated rENaC subunits ␣ P646stop , ␤ R564stop , and ␥ F606stop (36) and the mutant subunit ␤ S518C (37) were in pSD5 and were a gift of Drs. Bernard C. Rossier and Laurent Schild (Lausanne, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Liddle's syndrome mutations affect the cytoplasmic tail of ENaC subunits, altering or deleting a crucial PPPXY motif essential for interaction with WW domains of Nedd4-2 (and a homologue Nedd4-1) and degradation as well as for internalization via clathrin-coated pits (Schild et al 1995). The mutated ENaC channel subunits in Liddle's syndrome are no longer recycled, and the fraction at the luminal cell surface increases (Fig.…”
Section: Liddle's Syndromementioning
confidence: 99%